2016
DOI: 10.1177/1420326x16629725
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting household energy rebound: Perspectives from a multidisciplinary study

Abstract: In this paper, an interdisciplinary team of economists and anthropologists study the perplexing case of Norwegian households' heat pump ownership. The heat pump is a technology that has the potential to reduce electricity consumption by up to 25% compared to conventional electric heating, but, as we demonstrate in this study, when taken into use it results in little or no change in electricity consumption. To explain this large rebound effect, we use a quantitative economic analysis combined with qualitative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…For example, when asked to calculate monthly car costs, only 29% of respondents included depreciation of the initial investment 34 . This is further confirmed by empirical evidence for travel 35 and heating expenses 11,19 . In addition, the effect is likely to be exaggerated by the sunk cost effect, which is considered an expression of mental accounting 36 : having invested money on adopting an energy-efficient product, people feel compelled to use it more.…”
Section: Mental Accountingsupporting
confidence: 61%
See 2 more Smart Citations
“…For example, when asked to calculate monthly car costs, only 29% of respondents included depreciation of the initial investment 34 . This is further confirmed by empirical evidence for travel 35 and heating expenses 11,19 . In addition, the effect is likely to be exaggerated by the sunk cost effect, which is considered an expression of mental accounting 36 : having invested money on adopting an energy-efficient product, people feel compelled to use it more.…”
Section: Mental Accountingsupporting
confidence: 61%
“…This effect is more pronounced for energy-efficient products. One study found adopters of heat pumps to be unaware they were using them more intensively than the conventional heating, resulting in higher indoor temperature 19 . According to another study consumers incorrectly infer that high energy efficiency translates to low overall energy use, which may consequently lead them to use energy-efficient products more intensively 20 .…”
Section: Inattention and Misconceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 In recent studies of residents’ behaviour, using mixed-methods research has been shown to provide a fuller picture of the subject of the study. 42,43 The combination of survey results and interviews provided new insights regarding the goals to guide people’s lighting choices and behaviour. The qualitative results contributed the additional information needed to understand key factors that influence residents’ illumination choices.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts include policy initiatives such as the Climate Change Committee 'White Paper' [2], as well as research commissioned by the Department of Business, Energy, and Industrial Strategy [3-6] to better understand how and why particular heating technologies such as heating controls contribute (or do not contribute) to energy efficiency and carbon emissions. However, advanced energy-efficient heating technologies, designed to enable lower energy use in homes, are reportedly contributing to unintended increased energy use and uncomfortable indoor environments [7]. Policy measures regarding space heating have also historically-both in the UK and the European Union (EU)-largely been based on energy-efficient heating technology improvements, more efficient energy generation, and generation from renewable and nuclear sources.…”
Section: Introductionmentioning
confidence: 99%